Reading as a Tool for Enhancing English Second Language Learning of Ordinary Level Learners in Namibian Secondary Schools - Ithindi, Sylvia; Engelbrecht , Dr. Alta; de Jager , Dr Lizette (International Journal of Language and Literary Studies, 2022)
The purpose of this study was to investigate the contribution of reading towards English as Second Language learning at Ordinary Level in Namibian senior secondary schools. A qualitative methodology was used for the study, carried out through a case study investigation, which involved secondary school teachers and learners who were randomly selected. Data were collected using an open-ended questionnaires and semi-structured interviews. Thematic analysis yielded key themes on the role of reading in ESL, namely; reading experience and the use of textbooks to enhance reading. The findings indicate that reading is not developed as a culture for the majority of OL learners. As is the case with Higher Level, there are no prescribed reading materials for OL. The researchers argue that Namibians have not yet adopted reading as part of their culture, ultimately contributing immensely to the high failure rate of learners. The study recommends that concerted efforts need to be made to instill the love of reading in OL learners for them to reach the same level as HL learners.